Measurement of tremor transmission during microsurgery. Issue 4 (9th December 2015) - Verrelli, David I.; Qian, Yi; Wood, James; Wilson, Michael K.
Abstract: Background: Tremor is a major impediment to performing fine motor tasks, as in microsurgery. However, conventional measurements do not involve tasks representative of microsurgery. Method: We developed a low‐cost surgical simulator incorporating a force transducer capable of detecting and quantifying the effects of tremor upon high‐fidelity silicone replicas of cardiac vessels and substrate muscle. Experienced and trainee surgeons performed simulated anastomoses on this rig. We characterized procedures in terms of tremor intensity, based on Lomb–Scargle periodograms. Results: Distinctive force oscillations occurred at 8–12 Hz, characteristic of enhanced physiological tremor, yielding peaks in power spectral density. These early results suggest a significantly lower transmission of tremor to the operative field by the experienced surgeon in comparison to the trainees. Conclusions: This new device quantifies the action of tremor upon a manipulandum during a complex task, which may be used for assessment and providing feedback to trainee surgeons. Copyright © 2015 John Wiley & Sons, Ltd.